2022
DOI: 10.1158/0008-5472.can-21-2576
|View full text |Cite
|
Sign up to set email alerts
|

HotspotESR1Mutations Are Multimodal and Contextual Modulators of Breast Cancer Metastasis

Abstract: Constitutively active estrogen receptor α (ER/ESR1) mutations have been identified in approximately one-third of ER+ metastatic breast cancers. Although these mutations are known as mediators of endocrine resistance, their potential role in promoting metastatic disease has not yet been mechanistically addressed. In this study, we show the presence of ESR1 mutations exclusively in distant but not local recurrences in five independent breast cancer cohorts. In concordance with transcriptomic profiling of ESR1-mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 66 publications
2
31
0
Order By: Relevance
“…The frequent occurrence of ER mutations in hormone therapy-resistant ER-positive metastatic breast cancer has led to intense research efforts to elucidate the molecular and phenotypic effects of ER mutations and to identify vulnerabilities in ER mutant cancers that could be exploited to develop effective therapies for hormone therapy-resistant tumors (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In a previous study, we used isogenic T-47D models expressing the Y537S or D538G ER mutations from the endogenous ER locus to show that ER mutations regulated the differential expression of thousands of genes and that these transcriptional changes were accompanied by phenotypic changes, including increased migration, invasion, and proliferation (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequent occurrence of ER mutations in hormone therapy-resistant ER-positive metastatic breast cancer has led to intense research efforts to elucidate the molecular and phenotypic effects of ER mutations and to identify vulnerabilities in ER mutant cancers that could be exploited to develop effective therapies for hormone therapy-resistant tumors (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In a previous study, we used isogenic T-47D models expressing the Y537S or D538G ER mutations from the endogenous ER locus to show that ER mutations regulated the differential expression of thousands of genes and that these transcriptional changes were accompanied by phenotypic changes, including increased migration, invasion, and proliferation (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Structural changes in ER's LBD as a result of ER LBD mutations confer an active conformation and ligand-independent activity to unliganded mutant ER, which drives large transcriptional changes in the absence of estrogens (5,7,9,(11)(12)(13)(14)(15)(16). Several studies have shown that this dramatic change in gene expression can drive increased cellular proliferation, invasion, and metastasis in breast cancer cells expressing mutant ER (4,5,9,13,14,(16)(17)(18). Recently, we showed that over half of these gene expression changes are driven directly by the constitutive activity of ER (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have identified genes that can be used as prognostic markers by CTC detection, including HER2, ESR1, PI3KCA, PSMA, MYC, TP53 and so on [173][174][175][176]. Several studies have demonstrated the feasibility of evaluating HER2 status of CTCs in BC using CellSearch ® [136,177,178].…”
Section: Studies Based On Molecular Characteristics Of Ctcmentioning
confidence: 99%
“…In ESR1-mut breast cancer, research demonstrates further genomic dysregulation and downstream signaling modulation that could be leveraged, including aberrant DNA bindings cofactors FOXA1 and CTCF, 41 NOTCH signaling, 41 and Wnt signaling. 135 …”
Section: Novel Hormonal Therapies and Clinical Opportunitiesmentioning
confidence: 99%